2020
DOI: 10.35595/2414-9179-2020-2-26-253-263
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of dangerous shore processes of Tsimlyansk Reservoir using GIS-technologies

Abstract: In the article, the degree of displaying dangerous exogenetic geological processes (abrasion, landslide, erosion) of the Tsimlyansk Reservoir at the present stage of reforming its shores is assessed. A new original methodology for monitoring morphological and morphometrical characteristics of different shore types of the reservoir, using unmanned aerial vehicles (UAV) and Agisoft Photoscan tooling is proposed. For a number of shore sections of the Tsimlyansk reservoir, assessment of consequence for stirring up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The main difference between these two calculations can be seen in areas with lakes that have a muddy environment. Due to the summer conditions, the areas of water bodies significantly decreased, which can be seen in results obtained using deep neural network [30]. Compared with the current approach, the methodology presented in previous research, based on mNDW I calculations, showed less accurate results.…”
Section: Training Configurationmentioning
confidence: 67%
“…The main difference between these two calculations can be seen in areas with lakes that have a muddy environment. Due to the summer conditions, the areas of water bodies significantly decreased, which can be seen in results obtained using deep neural network [30]. Compared with the current approach, the methodology presented in previous research, based on mNDW I calculations, showed less accurate results.…”
Section: Training Configurationmentioning
confidence: 67%